2012
DOI: 10.1016/j.trc.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Visibility monitoring using conventional roadside cameras – Emerging applications

Abstract: The measurement of atmospheric visibility is an important element for road and air transportation safety. We propose in this paper a novel estimator of the atmospheric visibility by already existing conventional highway cameras, with a technique based on the gradient magnitude selected by applying Lambert's law with respect to changes in lighting conditions. The response of this estimator is calibrated by non-linear regression with data from a visibility meter installed in a test site which has been instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 27 publications
1
40
0
2
Order By: Relevance
“…Importantly, the OpenAQ system checks each data source for updated information every 10 min, which guarantees that the data will be available from the platform almost immediately after they are published by the original data providers. In Europe, OpenAQ currently provides PM 10 and PM 2.5 data from about 1800 and 800 locations, respectively. The hackAIR data collection framework retrieves up-to-date information from each location by regularly performing appropriate queries to the Representation State Transfer (REST) API provided by OpenAQ.…”
Section: Environmental Data Discovery and Indexingmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the OpenAQ system checks each data source for updated information every 10 min, which guarantees that the data will be available from the platform almost immediately after they are published by the original data providers. In Europe, OpenAQ currently provides PM 10 and PM 2.5 data from about 1800 and 800 locations, respectively. The hackAIR data collection framework retrieves up-to-date information from each location by regularly performing appropriate queries to the Representation State Transfer (REST) API provided by OpenAQ.…”
Section: Environmental Data Discovery and Indexingmentioning
confidence: 99%
“…Particulate matter up to 10 micrometers in diameter (PM 10 ) is able to penetrate the bronchi, while particulate matter with diameter up to 2.5 micrometers (PM 2.5 ) can penetrate the lungs and enter the circulatory system [3]. The International Agency for Research on Cancer (IARC) concluded in 2013 that particulate matter is carcinogenic to humans [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massively distributed visual sensors (webcams) are utilized for phenology study, scene and environment understanding [19,6]. A multi-tier network SensEye of heterogeneous cameras has been proposed to overcome the disadvantage of singletier networks in surveillance application, performing object detection, recognition and tracking tasks [25].…”
Section: Event Detection Using Visual Sensorsmentioning
confidence: 99%
“…[14] proposed to use a homomorphic filter or a Haar function in addition to the high-pass filter in order to reduce the effects of nonuniform illumination. [3] proposed a visibility descriptor which is robust to illumination variations by making use of Lambertian surfaces only. However, the method to select the Lambertian surfaces is superfificially justified.…”
Section: Introductionmentioning
confidence: 99%